Peningkatan Keterampilan Pembuatan Produk Olahan Pada Ibu-Ibu RT 02 RW 02 Desa Sambirejo Kecamatan Saradan Kabupaten Madiun - Sri Rahayu; Praptiningsih Gamawati Adinurani; Djoko Setyo Martono (Universitas Merdeka Madiun, 2024)
Processed Product Skills Improvement Program are carried out by empowering women in soybean sorting groups. The women of RT 02 RW 02 Sambirejo Village, Saradan District, and Madiun Regency have only participated in a partnership program with PT Unilever as sorters. Experience and skills as a sorter have yet to follow the knowledge about the added value of soybeans as a processed product. This program aims to increase the knowledge and skills of the sorting group in producing processed products. The service method uses socialization and counseling on post-harvest management, training, mentoring, and monitoring the manufacture of processed soy sauce products. The results of program implementation show that program activities were carried out well. Discussion activities, program evaluation, counseling, and mentoring can increase members' knowledge and ability to make processed soy sauce products independently. Processed products can meet the family's nutritional needs and commercially can increase income and, in the future, make Sambirejo Village a soy sauce production center.